Pediatric Subcutaneous Panniculitis-Like T-Cell Lymphoma with Favorable Result by Immunosupressive Therapy: A Report of Two Cases. (1st September 2014) - Nagai, Kozo; Nakano, Naoko; Iwai, Tsuyako; Iwai, Asayuki; Tauchi, Hisamichi; Ohshima, Kouichi; Ishii, Eiichi
<x xml:space="preserve">Abstract</x> Subcutaneous panniculitis-like T-cell lymphoma (SPTL) is a rare type of skin lymphoma. Histopathology mimicking a lobular panniculitis makes it difficult to distinguish SPTL from benign autoimmune disease. We present cases of a 10-year-old female and an 11-year-old male with SPTL showing recurrent panniculitis and systemic manifestations. Initially, antibiotics and steroids were administered to treat infectious disease and benign panniculitis. However, they experienced recurrent fever and erythema nodosum. Additional immunohistochemistry and T-cell receptor (TCR) gene rearrangement analyses were performed, enabling the establishment of an SPTL diagnosis. The affected patients were given immunosuppressive therapy with favorable results.